A proteomic overview of the major venom components from Tityus championi from Panama. (May 2023) - Salazar, Marcos H.; Ortíz, Magdalena Hernández; Encarnación, Sergio; Zamudio, Fernando; Possani, Lourival D.; Cleghorn, John; Morán, Maricruz; Acosta, Hildaura; Corzo, Gerardo
Abstract: In recent years, morbidity caused by scorpion sting of the species Tityus championi has increased in Panama. Therefore, the LD50 was determined by intravenous injection in 2.9 mg/kg and the venom of T. championi was separated using a HPLC system and their fractions were tested for biological activities in mice to identify the most toxic fractions to mammals. In addition, the venom fractions were also tested against invertebrates to look for insect-specific toxin peptides. The most toxic fractions were analyzed by MS/MS spectrometry. The primary structures of T. championi venom peptides with the most relevant activity were obtained, and the primary structure of one of most neurotoxic peptides was found at least in other four species of Tityus from Panama. This neurotoxin is quite important to be used as a protein target to be neutralized if developing antivenoms against the sting of this Panamanian scorpion or other relevant species of genera Tityus in the country. Graphical abstract: Reverse-phase HPLC chromatogram of the venom from Tityus championi from Panama. Image 1